The VZV/IE63-specific T cell response prevents herpes zoster in fingolimod-treated patients. Issue 2 (April 2016) - Mathias, Amandine; Perriard, Guillaume; Canales, Mathieu; Vuilleumier, Fanny; Perrotta, Gaetano; Schluep, Myriam; Du Pasquier, Renaud
Abstract : Objective: To assess longitudinally the antiviral immune response of T cells from patients with multiple sclerosis (MS) treated with fingolimod (FTY) vs other disease-modifying treatments (DMTs). Methods: We assessed cellular immune responses specific to influenza virus (FLU), JC virus (JCV), and varicella-zoster virus (VZV) using quantification of interferon-γ secretion by enzyme-linked immunospot in patients with MS on FTY (n = 31), including 2 with herpes zoster (HZ), natalizumab (n = 11), and other DMTs (n = 11). We used viral lysates for FLU and VZV and a pool of peptides for FLU, JCV (VP-1), and VZV (IE63). Results: Besides an expected drop of T cells, we found that, proportionally to the number of CD3 + T cells, only FTY-treated patients with MS exhibited an increased VZV/IE63-specific T cell response peaking 6 months into treatment, a response that returned to baseline after 12 and 24 months. Two FTY-treated patients developed an HZ 6 months into treatment, coinciding with an absent VZV/IE63-specific T cell response. However, cellular immune responses specific to VZV lysate, JCV, and FLU (lysate and pool of peptide epitopes) were similar between all 3 categories (FTY, natalizumab, and other DMTs) of study patients. Conclusions: FTY-treated patients with MS exhibit an increased VZV/IE63-specific cellular immune response after 6 months of treatment. FTY-treated patients who develop an HZ are not able to mount such a response, suggesting that a T cell response directed against this viral protein may be key in preventing the occurrence of HZ.